Study of Air quality and Air pollution - Amrita (Innovative Research Thoughts, 2023)
A considerable number of Indian towns, including Rohtak, which is situated in the state of Haryana, are plagued by serious issues related to air pollution. Rohtak is one of these cities. The majority of Rohtak's air pollution can be traced back to a confluence of elements, the most prominent of which are emissions from industry, automobile traffic, and agricultural practises. The statistics provided by the Central Pollution Control Board (CPCB) indicate that Rohtak has a typically bad air quality, with an average Air Quality Index (AQI) that ranges from Unhealthy to Very Unhealthy during the course of the year. It is possible for the Air Quality Index (AQI) in Rohtak to reach Severe levels during the winter months, which may have a negative impact on the health of the people who live there. The administration of Rohtak has taken a number of steps to address the issue of air pollution in the city. These steps include the deployment of buses powered by compressed natural gas (CNG) and the shutting down of companies that contribute to air pollution. Using public transportation, carpooling, and cutting down on energy use at home are some of the efforts that people may take to cut down on the amount of pollution that they are responsible for contributing to the environment.